PENERAPAN MEDIA PUZZLE UNTUK MENINGKATKAN LITERASI MEMBACA PADA SISWA KELAS RENDAH - Novik Condrowati; Sutji Muljani; Suriswo Suriswo (JPDI (Jurnal Pendidikan Dasar Indonesia), 2026)
This study aims to determine the impact of using puzzle media on the comprehension and reading fluency of lower grade students. The research sample was 322 grade II students of Public Elementary Schools in KWK Petarukan, Pemalang Regency, which were divided into two groups, an experimental group of 157 students and a control group of 165 students with a saturated sample technique. The source of research data used was primary data obtained directly from respondents with tests, interviews and questionnaires. The data processing tool used was SPSS for Windows version 21. Data analysis used the paired sample T Test. From the data test and analysis carried out, this study provides empirical evidence as follows: the use of puzzle media can improve comprehension and reading fluency in lower grade students